2022
DOI: 10.1186/s12877-022-02796-z
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse childhood experiences and handgrip strength among middle-aged and older adults: a cross-sectional study in China

Abstract: Background Evidence on the association between adverse childhood experiences (ACEs) and handgrip strength (HGS) in later life was limited and inconclusive. We aimed to explore the impact of ACEs on HGS among middle-aged and older Chinese adults. Methods We conducted a cross-sectional study with data extracted from the China Health and Retirement Longitudinal Study (CHARLS), a nationally representative survey with respondents recruited from 450 vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Literature showed that childhood experiences are generally divided into three parts, that is, adverse childhood experiences (ACE) (Hu 2021;Lin et al 2022;Tao et al 2021), childhood socio-economic status (SES) (Tao et al 2021;Zhang & Lu 2021) and childhood health and healthcare (Pan 2020;Zhang & Lu 2021). The severer ACE elder people had experienced, the worse their health is, while better childhood SES and healthcare are the protective factors of health status in later life (Pan et al 2021;Tao et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Literature showed that childhood experiences are generally divided into three parts, that is, adverse childhood experiences (ACE) (Hu 2021;Lin et al 2022;Tao et al 2021), childhood socio-economic status (SES) (Tao et al 2021;Zhang & Lu 2021) and childhood health and healthcare (Pan 2020;Zhang & Lu 2021). The severer ACE elder people had experienced, the worse their health is, while better childhood SES and healthcare are the protective factors of health status in later life (Pan et al 2021;Tao et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that in Fig. 1 , the number of participants without data in the CHARLS 2014 survey should have been 1549 (instead of 2376); the figure should have appeared as shown below.…”
mentioning
confidence: 99%
“…Recent empirical evidence suggests that adverse family events can have an impact on both physical and mental health later in life (Thomeer & Ostergren Clark, 2021;Umberson & Thomeer, 2020). Collectively, these studies suggest that individuals with exposure to early-life adversities in the family domain have chronic stress and elevated allostatic load (e.g., Danese & McEwen, 2012;Lin et al, 2022;Nusslock & Miller, 2016). In turn, this is associated with increased levels of inflammation and dysfunction in the immune system (Danese & McEwen, 2012;Fagundes et al, 2013) which subsequently cause damage to skeletal muscle and lower physical functioning (Dalle et al, 2022;Kamper et al, 2021;Schaap et al, 2006).…”
Section: Children's Union Dissolution and Associations With Parental ...mentioning
confidence: 99%
“…Yet, disruptive family events could have an impact on both mental and physical health in later life (Thomeer & Ostergren Clark, 2021;Umberson & Thomeer, 2020). The extant evidence shows that exposure to adversities in the family domain can lead to increased levels of stress and allostatic load (Danese & McEwen, 2012;Lin et al, 2022;Nusslock & Miller, 2016), inflammation and dysfunction in the immune system (Danese & McEwen, 2012;Fagundes et al, 2013), which can, in turn, detrimentally affect muscular strength and physical functioning later in life (Dalle et al, 2022;Kamper et al, 2021;Schaap et al, 2006). Omitting the physical dimension of health may result in an incomplete picture of the impact of children's union dissolution on different dimensions of parental health.…”
Section: Introductionmentioning
confidence: 99%